2018
DOI: 10.1021/acs.energyfuels.8b01125
|View full text |Cite
|
Sign up to set email alerts
|

Combustion, Performance, and Emission Study of a Research Diesel Engine Fueled with Palm Oil Biodiesel and Its Additive

Abstract: More requirements for diesel fuel and a huge rise in air pollution, owing to the surplus usage of diesel fuel, give us a prospect to discover environmentally friendly and clean fuels for the existing unmodified diesel engines. The present work is aimed to analyze the combustion, performance, and emission characteristics of a neat palm oil biodiesel (POBD)-fueled diesel engine with silver oxide (Ag2O) as a additive in various mass fractions (5 and 10 ppm), and the results are compared to conventional diesel. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…NOx emissions from engines include nitrogen dioxide (NO 2 ) and nitric oxide (NO) gases formed at elevated combustion temperature by the chemical reaction between the nitrogen in the air and atmospheric oxygen [34]. NO variation of CBD, CBD25BC, diesel, and CBD50BC is shown in Fig.…”
Section: Oxides Of Nitrogen Emissionsmentioning
confidence: 99%
“…NOx emissions from engines include nitrogen dioxide (NO 2 ) and nitric oxide (NO) gases formed at elevated combustion temperature by the chemical reaction between the nitrogen in the air and atmospheric oxygen [34]. NO variation of CBD, CBD25BC, diesel, and CBD50BC is shown in Fig.…”
Section: Oxides Of Nitrogen Emissionsmentioning
confidence: 99%
“…The experimental findings exhibited that the addition of Ag 2 O particles to POME enhanced the combustion characteristics due to the increased surface area. Besides, the addition of Ag 2 O nanoparticles to POME resulted in enhanced brake thermal efficiency [46]. The findings also indicated that Ag 2 O nanoparticles improved the emission levels of smoke, NO x , HC, and CO [46].…”
Section: Microemulsionmentioning
confidence: 90%
“…Besides, the addition of Ag 2 O nanoparticles to POME resulted in enhanced brake thermal efficiency [46]. The findings also indicated that Ag 2 O nanoparticles improved the emission levels of smoke, NO x , HC, and CO [46]. Prabhu et al [41] reported on the influence of microemulsion on palm oil blending with conventional diesel.…”
Section: Microemulsionmentioning
confidence: 98%
See 1 more Smart Citation
“…The peak cylinder pressure is recorded as 74.69 bar by diesel fuel due to the lower viscosity, higher calori c value whereas B20 accounts 74.39 bar which is lower than diesel owing to higher viscosity and lower calori c value. (Devarajan et al 2018) The addition of nano particles with B20 helps to increase the cylinder pressure. It may be due to shorter ignition delay, higher calori c vale and higher heat transfer rate of nano particles.…”
Section: Cylinder Pressurementioning
confidence: 99%